ADVANTAGES OF THE EDUCATION SYSTEM IN THE UNITED STATES - Abayomi T; Aslam Shahriar (International Journal of Education and Social Science Studies, 2024)
The United States, a country with one of the largest economies in the world, is also known for its quality education system. Of course, there are many advantages to the education system in America compared to the education system in other countries. The method used by the author in conducting this research was a descriptive qualitative method with a literature document review. The advantages of the education system in America are (1) Literacy Culture, Literacy education does not only occur in schools, but also involves the role of parents and communities. Literacy culture is instilled in American families through reading with children at home (2) Math skills, At the elementary and secondary school levels, the United States adopts an approach that focuses on a core curriculum that includes subjects such as math, science, English and the arts. In addition, learners are also given the freedom to choose additional subjects according to their interests and talents (3) Practical and Authentic Learning, US education is also known for emphasizing practical and authentic learning that incorporates real-life lessons and activities (4) Character Development Programs Not only is academic success important, US education also focuses on student character development. These character development programs aim to promote positive behavior, global awareness, tolerance towards others, and most importantly, kindness and empathy in students. (5) Flexible Education System, Educational flexibility is one of the advantages of the higher education system in the United States that benefits international students. The US education system is one of the most diverse in the world. With flexibility, students can experiment with different study programs within the first two years of college education.